Comparison of oncological outcomes between extended and no pelvic lymph node dissection in patients with high- or very high-risk prostate cancer: a multi-institutional study - Satoshi Washino; Makoto Kawase; Masaki Shimbo; Takeshi Yamasaki; Kojiro Ohba; Jun Miki; Tomoaki Miyagawa; Takuya Koie (Prostate International, 2024)
Background: Despite providing valuable staging and prognostic information, the therapeutic benefit of pelvic lymph node dissection (PLND) remains uncertain. We sought to assess the effect of extended PLND (ePLND) on the biochemical recurrence (BCR) of patients with National Comprehensive Cancer Net (NCCN) high- or very high-risk prostate cancer treated via robot-assisted radical prostatectomy (RARP). Methods: We used a multi-institutional database (six centers) to assess 989 patients who underwent RARP from 2014 to 2022 with or without ePLND, among which 699 patients underwent BCR analysis. We performed 1:1 propensity score matching to account for potential differences between the two groups and compared them in terms of BCR-free survival. Cox's regression models were used to test the effect of ePLND on BCR. Results: A total of 585 patients underwent ePLND and 404 did not. A median of 19 lymph nodes was removed in the ePLND cohort. After propensity score matching, no significant differences in BCR-free survival were observed between the two cohorts (HR 1.108, 95% CI 0.776–1.582, p = 0.556). Multivariable Cox's regression models adjusted for the preoperative and postoperative tumor characteristics revealed that PLND was not an independent predictor of BCR. Conclusion: No significant differences in BCR-free survival were observed between NCCN high- or very high-risk prostate cancer patients who underwent PLND during RARP and those who did not. The therapeutic utility of PLND thus remains unclear.